THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF ORGANIZING AND IMPROVING THE EDUCATIONAL PROCESS IN INTERIOR DESIGN AT VOCATIONAL EDUCATIONAL ESTABLISHMENTS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the current state of teaching the subject “Interior design of buildings” in vocational education establishments, its theoretical and methodological foundations, and ways to improve the educational process. Based on pedagogical and psychological sources, the specific features of interior design education are analyzed and proposals are developed for integrating creative methodologies into the teaching process.